2007
DOI: 10.1097/01.anes.0000267593.72744.20
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Variations in Pulse Oximetry Plethysmographic Waveform Amplitude to Predict Fluid Responsiveness in the Operating Room

Abstract: DeltaPOP can predict fluid responsiveness noninvasively in mechanically ventilated patients during general anesthesia. This index has potential clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
119
2
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(133 citation statements)
references
References 30 publications
1
119
2
7
Order By: Relevance
“…Another new device (Masimo Radical TM 7 system, Masimo Co., Irvine, CA, USA) can automatically display perfusion index (PI) and calculate the pleth variability index (PVI), which is a new algorithm that automatically calculates ΔPOP. But the ability of PVI to predict fluid responsiveness was evaluated in mechanically ventilated patients preoperatively (12)(13)(14) or after passive leg rising in spontaneously breathing volunteers (15). Whether these two indices can be used for intraoperative fluid responsiveness predictions and fluid optimization in patients undergoing major surgical procedures still has to be demonstrated, and the optimal threshold value of these indices in the surgical setting still has to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another new device (Masimo Radical TM 7 system, Masimo Co., Irvine, CA, USA) can automatically display perfusion index (PI) and calculate the pleth variability index (PVI), which is a new algorithm that automatically calculates ΔPOP. But the ability of PVI to predict fluid responsiveness was evaluated in mechanically ventilated patients preoperatively (12)(13)(14) or after passive leg rising in spontaneously breathing volunteers (15). Whether these two indices can be used for intraoperative fluid responsiveness predictions and fluid optimization in patients undergoing major surgical procedures still has to be demonstrated, and the optimal threshold value of these indices in the surgical setting still has to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…PI depends on vasomotor tone and sympathetic tone, which may affect the pulsatile absorption component (23 (14). This may be related to a decrease in sympathetic tone related to general anaesthesia and vasomotor tone does not impact PVI (12,13). The accuracy of PVI to predict fluid responsiveness was improved on analyzing patients with higher PI values (25).…”
Section: Changes In Hemodynamic Variables After Volume Expansionmentioning
confidence: 99%
“…Variations of heart rate (HR) and blood pressure (BP), even if absolutely not sensitive nor specific, have been used by anesthesiologists for decades for assessing individual needs for intravascular volume administration, analgesic drugs, hypnotic drugs, and vasoactive drugs. Some more specific informations have been derived from these simplistic signals in order to more specifically predict a state of pre-load dependency, like the deltaPP index which is derived from the continuous blood pressure signal [14] and the variations in the amplitude of the non-invasive photoplethysmographic (SpO2) signal [15].…”
Section: Introductionmentioning
confidence: 99%
“…Canneson et al noted that respiratory modulation of the PPG signal in ventilated patients reduces when intravenous fluids are given and suggest that the relative modulation of the PPG signal may be used as an indication of 'fluid responsiveness' (the increase in blood pressure after administration of a given volume of intravenous fluid) [7]. Gesquiere et al demonstrated that the respiratory modulation increases when 450 mL of blood is removed from the patient [8].…”
Section: Introductionmentioning
confidence: 99%